Zirconia-reinforced alumina ceramic sintered body

JP7639127B2Active Publication Date: 2025-03-04HERAEUS CONAMIC NORTH AMERICA LLC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023518192
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-10-15
Filing Date
2021-10-14
Publication Date
2025-03-04
Estimated Expiration
2041-10-14

Smart Images

  • Figure 0007639127000008
    Figure 0007639127000008
  • Figure 0007639127000009
    Figure 0007639127000009
  • Figure 0007639127000010
    Figure 0007639127000010
Patent Text Reader

Abstract

1. A sintered ceramic body having at least one surface, the sintered ceramic body comprising a first crystalline phase comprising Al2O3 and a second crystalline phase comprising 8 volume % to 20 volume % ZrO2, the first crystalline phase being a continuous matrix and the second crystalline phase being dispersed in the continuous matrix, the sintered ceramic body having pores with a maximum pore size of 0.1 to 5 μm as measured by SEM, and the sintered ceramic body having a pore size of 6.899 to 9.630 × 10 over a temperature range of 25-200°C to 25-1400°C as measured in accordance with ASTM E228-17. -6 / °C, wherein the sintered ceramic body has a relative density of 99% to 100%, a density variation of less than 0.2 to 5% across its greatest dimension, the greatest dimension being 200 to 625 mm, and wherein Si is either absent from the sintered ceramic body or present in the sintered ceramic body in an amount of 100 ppm or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to sintered ceramic compositions comprising alumina and zirconia that exhibit high strength and low loss of RF transmission when used as components in semiconductor processing tools. These may be components such as chamber liners, RF or microwave transparent windows, showerheads, focus rings, wafer chucks, gas injectors or nozzles, shield rings, clamp rings, mixing manifolds, and gas distribution assemblies. The present disclosure also relates to methods of preparing the sintered ceramic compositions. [Background technology]

[0002] Alumina-based sintered bodies have excellent heat resistance, chemical resistance, plasma resistance, and thermal conductivity, and have a small dielectric loss tangent (tan δ) in the high frequency range. Therefore, alumina-based sintered bodies are used, for example, as members for plasma processing equipment, etchers for manufacturing semiconductors and liquid crystal displays, CVD equipment, etc., or as substrates for plasma-resistant members to be coated.

[0003] Although various proposals have been made to improve the corrosion resistance and dielectric loss tangent (dielectric loss) of alumina-based sintered bodies, there remains a need in the art for alumina-based sintered bodies that combine corrosion resistance, high thermal conductivity, and low dielectric loss properties, and are suitable as substrates on which dense films can be uniformly deposited. There is also a need in the art for alumina-based sintered bodies that meet these performance requirements, but are also large enough to fabricate components with large dimensions, e.g., maximum dimensions exceeding 200 mm to 600 mm. Summary of the Invention

[0004] These and other needs are addressed by the various embodiments, aspects, and configurations disclosed herein.

[0005] 1. A sintered ceramic body having at least one surface, the sintered ceramic body comprising a first crystalline phase comprising Al2O3 and a second crystalline phase comprising 8 vol.% to 20 vol.% ZrO2, the first crystalline phase being a continuous matrix and the second crystalline phase being dispersed in the continuous matrix, the sintered ceramic body having pores with a maximum pore size of 0.1 to 5 μm as measured by SEM, and the sintered ceramic body has a porosity of 6.899 to 9.630 x 10 over a temperature range of 25-200°C to 25-1400°C as measured according to ASTM E228-17. -6 1. A sintered ceramic body having a thermal expansion coefficient of 100 / °C, wherein the sintered ceramic body has a relative density of 99%-100% and has a density variation of less than 0.2-5% across its greatest dimension, the greatest dimension being 200-625 mm, and wherein Si is either absent in the sintered ceramic body or present in the sintered ceramic body in an amount of 100 ppm or less.

[0006] Embodiment 2. The sintered ceramic body of embodiment 1, wherein the second crystalline phase is present in an amount of 12-25%.

[0007] Embodiment 3. The sintered ceramic body of any one of the preceding embodiments, wherein the second crystalline phase is present in an amount of 5-15 volume percent of the sintered ceramic body.

[0008] Embodiment 4. The sintered ceramic body of any one of the preceding embodiments, wherein Si is present at 14-100 ppm.

[0009] Embodiment 5. A sintered ceramic body according to any one of embodiments 1 to 3, wherein Si, if present, is present at 14 ppm or less.

[0010] Embodiment 6. The sintered ceramic body of any one of the preceding embodiments, having a total impurity content of the trace elements Li, Na, Mg, K, Ca, B, P, Fe, Cu, Cr, Zn, In, Sn, and Sb (combined) of 50 ppm or less as measured by ICPMS.

[0011] Embodiment 7. The sintered ceramic body of any one of the preceding embodiments, having a total impurity content of the trace elements Li, Na, Mg, K, Ca, B, P, Fe, Cu, Cr, Zn, In, Sn, and Sb (combined) of 15 ppm or less as measured by ICPMS.

[0012] Embodiment 8. The sintered ceramic body of any one of the preceding embodiments, wherein the maximum pore size is from 0.1 to 3 μm as measured by SEM.

[0013] Embodiment 9. The sintered ceramic body of any one of the preceding embodiments, wherein the maximum pore size is from 0.1 to 1 μm as measured by SEM.

[0014] Embodiment 10. The sintered ceramic body of any one of the preceding embodiments, wherein the sintered ceramic body has a relative density of 99% to 99.99%.

[0015] Embodiment 11. The sintered ceramic body of any one of the preceding embodiments, wherein the sintered ceramic body has an arithmetic mean height (Sa) of the unetched areas of 3 to 20 nm.

[0016] Embodiment 12. The sintered ceramic body of any one of the preceding embodiments, having a maximum height Sz of 0.05 to 1.5 um in the unetched areas according to section 4.1.7 of ISO standard 25178-2-2012.

[0017] 13. 6.685 to 9.630 × 10 over the temperature range from 25 to 200 ° C to 25 to 1400 ° C -6 3. The sintered ceramic body of any one of the preceding embodiments, having a thermal expansion coefficient of 1.0 / °C.

[0018] Embodiment 14. The sintered ceramic body of any one of the preceding embodiments, having a purity of 99.985% and higher.

[0019] Embodiment 15. The sintered ceramic body of any one of the preceding embodiments, having a thermal conductivity at ambient temperature of about 27 W / mK, as measured according to ASTM E1461-13.

[0020] Embodiment 16. The sintered ceramic body of any one of the preceding embodiments, having a thermal conductivity of about 14 W / mK at 200° C., as measured according to ASTM E1461-13.

[0021] Embodiment 17. A second crystalline phase comprising ZrO2 is present at 14% to 18% by volume, and has a thermal expansion coefficient of 7.520 to 9.558 x 10 over the temperature range of 25-200°C to 25-1400°C, as measured according to ASTM E228-17. -6 3. The sintered ceramic body of any one of the preceding embodiments, wherein the temperature is 0.15 to 1.5° C.

[0022] Embodiment 18. A second crystalline phase comprising ZrO2 is present at 16 volume percent and has a thermal expansion coefficient of 7.711 to 9.558 x 10 over the temperature range of 25-200°C to 25-1400°C, as measured according to ASTM E228-17. -6 3. The sintered ceramic body of any one of the preceding embodiments, wherein the temperature is 0.15 to 1.5° C.

[0023] Embodiment 19. A method of making a sintered ceramic body, comprising the steps of: a) combining aluminum oxide powder and zirconium oxide powder to make a powder mixture, the aluminum oxide powder and the zirconium oxide powder each having a total impurity content of less than 150 ppm; b) sintering the powder mixture by heating to raise the temperature of the powder mixture to a sintering temperature of 600°C to 1400°C and maintaining the sintering temperature for a period of 4 to 12 hours to form a sintered powder mixture; and c) disposing the sintered powder mixture within a volume defined by a toolset of a sintering apparatus to create a vacuum condition within the volume, the toolset comprising a graphite die defining a volume, an inner wall, first and second openings, and first and second punches operatively coupled to the die, each of the first and second punches having an outer wall defining a diameter less than a diameter of the inner wall of the die. %-20% by volume of the sintered ceramic body, the sintered ceramic body having at least one surface, the sintered ceramic body comprising a first crystalline phase comprising Al2O3 and a second crystalline phase comprising 8%-20% by volume of ZrO2, the first crystalline phase being a continuous matrix and the second crystalline phase being dispersed in the continuous matrix, the sintered ceramic body having pores having a maximum pore size of 0.1-5 μm as measured by SEM, and the sintered ceramic body having a pore size of 10 μm-100 μm as measured by SEM according to ASTM A12464. 6.899 to 9.630 × 10 over the temperature range from 25 to 200 °C to 25 to 1400 °C, measured according to E228-17 -6 / °C, the sintered ceramic body has a relative density of 99%-100%, has a density variation of less than 0.2-5% across its greatest dimension, the greatest dimension being 200-625 mm, and Si is either absent in the sintered ceramic body or present in the sintered ceramic body in an amount of 100 ppm or less.

[0024] Embodiment 20. The method of embodiment 19, wherein the powder mixture of step a) comprises zirconium oxide in an amount such that the sintered ceramic body has 5-25% by volume zirconia.

[0025] Embodiment 21. The method of embodiment 19 or 20, further comprising the steps of: f) annealing the sintered ceramic body by applying heat to increase the temperature of the sintered ceramic body until an annealing temperature is reached; and g) reducing the temperature of the annealed sintered ceramic body.

[0026] Embodiment 22.h) The method of any one of embodiments 19-21, further comprising machining the sintered ceramic body to produce sintered ceramic components in the form of a dielectric window or RF window, a focus ring, a nozzle or gas injector, a showerhead, a gas distribution plate, an etching chamber liner, a plasma source adapter, a gas inlet adapter, a diffuser, an electronic wafer chuck, a chuck, a puck, a mixing manifold, an ion suppressor element, a faceplate, an isolator, a spacer, and / or a guard ring in an etching chamber.

[0027] Embodiment 23. The method according to any one of embodiments 19 to 22, wherein the sintering temperature is 1000 to 1300°C.

[0028] Embodiment 24. The method of any one of embodiments 19 to 23, wherein a pressure of 5 to 59 MPa is applied to the sintered powder mixture while heating to the sintering temperature.

[0029] Embodiment 25. The method according to embodiment 24, wherein the pressure is 5 to 40 MPa.

[0030] Embodiment 26. The method according to embodiment 25, wherein the pressure is 5 to 20 MPa.

[0031] Embodiment 27. A sintered ceramic body made by the method of any one of embodiments 19-26.

[0032] The embodiments of the present invention may be used alone or in combination with each other. [Brief description of the drawings]

[0033] [Figure 1] 1 is a 5000x SEM micrograph showing zirconia distributed in an alumina matrix. [Diagram 2] 1 is a plot of thermal expansion coefficients comparing compositions having various amounts of zirconia over the temperature range from 25-200° C. to 25-1400° C. [Diagram 3] 1 is a SEM micrograph (5000x) of the surface of a sintered ceramic body disclosed herein that contains 16% by volume ZrO2. [Figure 4] 1 is a plot of pore area versus pore size for the surface of a sintered ceramic body disclosed herein containing 16 volume percent ZrO2. [Diagram 5] 1 is a graph showing an XRD pattern of the surface of a sintered ceramic body disclosed herein containing 15 volume % ZrO2. [Figure 6] 1 is a graph showing the total area of ​​secondary crystalline phase by size and frequency. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0034] Reference will now be made in detail to certain embodiments. Examples of certain embodiments are illustrated in the accompanying drawings. Although the invention will be described in conjunction with these specific implementations, it will be understood that it is not intended to limit the invention to such specific embodiments. On the contrary, the disclosure is intended to cover alternatives, modifications, and equivalents that may be included within the spirit and scope of the invention as defined by the appended claims. In the following description, numerous specific details are set forth in order to provide a thorough understanding of the disclosed embodiments. The invention may be practiced without some or all of these specific details.

[0035] definition As used herein, the term "alumina" is understood to be aluminum oxide, including Al2O3.

[0036] As used herein, the term "yttria" is understood to be yttrium oxide, including Y2O3.

[0037] As used herein, the term "silica" is understood to be silicon dioxide, including SiO2.

[0038] As used herein, the terms "semiconductor wafer," "wafer," "substrate," and "wafer substrate" are used interchangeably. Wafers or substrates used in the semiconductor device industry typically have a diameter of 200 mm, or 300 mm, or 450 mm.

[0039] As used herein, the term "sintered ceramic body" is synonymous with "sinter," "body," or "sintered body" and refers to a solid ceramic article formed from the powder mixtures disclosed herein when subjected to pressing and heat treatment processes that create a monolithic body from the powder mixture.

[0040] As used herein, the term "purity" refers to the presence of various contaminants in the bulk starting materials from which the powder mixture may be formed, as well as in the powder mixture after processing, and in the sintered ceramic bodies disclosed herein. Contaminants or "impurities" are considered to be those that may interfere with the intended application. For example, some elements or compounds such as HfO2 that may be present in the starting zirconia powder may not be considered contaminants due to their very similar chemical behavior to ZrO2, and therefore may not be considered when reporting purity. Y2O3 may be added to zirconia as a phase transition stabilizer, and therefore may not be considered when reporting purity. Higher purities (closer to 100%) represent materials that are essentially free of or contain very small amounts of contaminants or impurities, and substantially contain the material composition present in the disclosed starting powders.

[0041] As used herein, the term "impurities" refers to compounds / contaminants present in a) the starting materials from which the powder mixture may be formed, b) the powder mixture after processing, and c) the sintered ceramic body, including impurities other than the starting materials themselves, including Zr, Al, and O, and optionally dopants, but not intentionally added elsewhere. Impurities may arise from the starting materials, powder processing, and / or sintering, and may adversely affect the properties of the sintered ceramic bodies disclosed herein. ICPMS methods were used to determine the impurity content of the powders, powder mixtures, and formed layers of the sintered bodies disclosed herein.

[0042] As used herein, the term "dopant" refers to a substance that is added to a bulk material to impart desired properties to the ceramic material (e.g., to alter electrical properties). Typically, dopants, when used, are present in low concentrations, i.e., >0.002% to <0.05% by weight.

[0043] Impurities differ from dopants in that dopants, as defined herein, are compounds that are intentionally added to a starting powder or powder mixture to obtain particular electrical, mechanical, optical, or other properties, such as, for example, modifying grain size in a multilayer sintered ceramic body.

[0044] As used herein, the term "volume porosity" may be synonymous with "porosity" as the level of porosity within the bulk ceramic represents the porosity on the surface.

[0045] As used herein, the term "sintered ceramic body component" refers to a sintered ceramic body after a machining step to produce the particular form or shape required for use in a semiconductor processing chamber.

[0046] As used herein, the term "powder mixture" refers to one or more powders mixed together prior to the sintering process, and thereby formed into a "sintered ceramic body" after the sintering step.

[0047] As used herein, the term "tool set" may include a die and two punches, and optionally additional spacer elements.

[0048] The terms "phase" or "crystalline phase" are synonymous and, as used herein, are understood to mean an ordered structure that forms the crystal lattice of a material, including a stoichiometric or compound phase or a solid solution phase. As used herein, a "solid solution" is defined as a mixture of different elements that share the same crystal lattice structure. The mixture in the lattice may be substitutional, where atoms of one starting crystal substitute for atoms of the other starting crystal, or interstitial, where atoms occupy positions normally vacant in the lattice.

[0049] As used herein, the terms "stiffness" and "rigidity" are synonymous with and consistent with the definition of Young's modulus as known to those skilled in the art.

[0050] The term "calcination", when used in reference to a heat treatment process, is understood herein to mean a heat treatment step that can be performed on powders in air at temperatures below the sintering temperature to remove moisture and / or impurities, increase crystallinity, and in some cases modify the powder mixture surface area.

[0051] As applied to ceramic heat treatment, the term "annealing" is understood herein to mean a heat treatment in which the disclosed sintered ceramic bodies or sintered ceramic body components are brought to a constant temperature and allowed to cool gradually to relieve stresses and / or normalize stoichiometry. Often, air or oxygen-containing environments can be used, although other atmospheres such as vacuum, inert and reducing are also possible.

[0052] As used herein, the term "about" when used in connection with a number allows for a variance of plus or minus 10%.

[0053] The following detailed description assumes that the embodiments are performed in an apparatus such as an etching or deposition chamber required as part of the fabrication of a semiconductor wafer substrate. However, the present disclosure is not so limited. The workpieces may be of various shapes, sizes, and materials. In addition to semiconductor wafer processing, other workpieces that may utilize the embodiments disclosed herein include various articles such as inorganic circuit boards with fine feature sizes, magnetic recording media, magnetic recording sensors, mirrors, optical elements, micromechanical devices, and the like.

[0054] composition The following detailed description assumes that the invention is implemented in an apparatus such as an etching or deposition chamber required as part of the fabrication of a semiconductor wafer substrate. However, the disclosure is not so limited. The workpieces may be of various shapes, sizes, and materials. In addition to semiconductor wafer processing, other workpieces that may utilize the invention include various articles such as inorganic circuit boards with fine feature sizes, magnetic recording media, magnetic recording sensors, mirrors, optical elements, micromechanical devices, and the like.

[0055] During the processing of semiconductor devices, corrosion resistant parts or chamber components are used in etch and deposition chambers and are exposed to harsh corrosive environments that cause the release of particles into the etch chamber, resulting in yield loss due to wafer level contamination. The sintered ceramic bodies and related components disclosed herein provide improved plasma etch resistance and enhanced ability to be cleaned within semiconductor processing chambers due to certain material properties and characteristics described below.

[0056] Semiconductor processing reactors associated with etching or deposition processes require chamber components to be fabricated from materials that are highly resistant to chemical attack by the reactive plasmas required for semiconductor processing. These plasma or process gases are often selected from the group consisting of O2, F, Cl2, HBr, BCl3, CCl4, and HCl. 4、 N 2、 NF3, NO, NO, C2H 4、 CF4, SF6, C4F8, CHF 3,The corrosion resistant materials disclosed herein may be composed of various halogen, oxygen and nitrogen based chemicals such as CH2F2. The use of the corrosion resistant materials disclosed herein provides reduced chemical corrosion during use. Furthermore, providing a chamber component material such as a sintered ceramic body with very high purity provides a uniform corrosion resistant body with few impurities that may act as initiation sites for corrosion. High resistance to erosion or spalling is also required for materials for use as chamber components. Erosion or spalling may result from ion bombardment of the component surface from the use of inert plasma gases such as Ar. Those materials with high hardness values ​​may be preferred for use as components because their enhanced hardness values ​​provide greater resistance to ion bombardment and resulting erosion. Furthermore, components made from dense materials with minimal porosity distributed on a fine scale may provide greater resistance to corrosion and erosion during etching and deposition processes. As a result, preferred chamber components may be those made from materials with high erosion and corrosion resistance during plasma etching, deposition and chamber cleaning processes. This resistance to corrosion and erosion prevents the release of particles from the component surface into the etching or deposition chamber during semiconductor processing. The emission or entrainment of such particles into the process chamber contributes to wafer contamination, semiconductor process drift and semiconductor device level yield loss.

[0057] In addition, chamber components must have sufficient bending strength and rigidity for the handling required during component installation, removal, cleaning, and use in the process chamber. High mechanical strength allows for machining of intricate features of fine geometry into the sintered ceramic body without breakage, cracking, or chipping. Bending strength or rigidity becomes especially important with the large component sizes used in modern process tools. Some component applications, such as dielectric or RF windows used in semiconductor processing chambers with diameters on the order of 200-620 mm or 625 mm, subject the window to significant stresses during use under vacuum conditions, necessitating the selection of high strength and rigidity corrosion resistant materials, or sintered ceramic bodies disclosed herein for use as substrates.

[0058] To improve plasma generation efficiency, especially at the high frequencies of 1 MHz to 20 GHz used in plasma processing chambers, the semiconductor chamber components are preferably made of materials with as low a dielectric loss as possible. Heat generated by absorption of microwave energy in these component materials with higher dielectric loss can cause uneven heating and increased thermal stresses on the components, and the combination of thermal and mechanical stresses during use can limit and complicate product design.

[0059] To meet the requirements, a sintered ceramic body having at least one surface, the sintered ceramic body comprising a first crystalline phase comprising Al2O3 and a second crystalline phase comprising 8 volume % to 20 volume % ZrO2, the first crystalline phase being a continuous matrix and the second crystalline phase being dispersed in the continuous matrix, the sintered ceramic body having pores with a maximum pore size of 0.1 to 5 μm as measured by SEM, and the sintered ceramic body having a pore size of 6.899 to 9.630 × 10 over a temperature range of 25-200 °C to 25-1400 °C as measured in accordance with ASTM E228-17. -6Disclosed herein is a sintered ceramic body having a thermal expansion coefficient of 100 / ° C., the sintered ceramic body having a relative density of 99%-100%, a density variation of less than 0.2-5% across the greatest dimension, the greatest dimension being 200-625 mm, and Si being either absent in the sintered ceramic body or present in the sintered ceramic body in an amount of 100 ppm or less. Compositions comprising a mixture of alumina and zirconia are sometimes referred to herein as "zirconia toughened alumina" or "ZTA."

[0060] In an embodiment illustrated by Figure 1, the sintered ceramic body disclosed herein has a matrix or composite structure of two or more discrete or continuous phases, where a first crystalline phase comprises Al2O3 and a second crystalline phase comprises ZrO2, the first crystalline phase being a continuous matrix and the second crystalline phase being dispersed in the continuous matrix. In Figure 1, the distinct zirconia crystalline phase (white) is uniformly distributed throughout the alumina crystalline matrix (black), meaning that to the extent that there are larger regions of discontinuous zirconia phase, the discontinuous zirconia phase comprises a maximum dimension of 15 μm or less, preferably 10 μm or less, preferably 8 μm or less, preferably 5 μm or less, preferably 3 μm or less, preferably 1 μm or less across a polished surface having an area of ​​54 μm x 54 μm. In embodiments, the zirconia crystalline phase is present in the sintered ceramic body in an amount between 8% and 20% by volume, and in some embodiments between 12% and 25% by volume, or between 5% and 25% by volume, or between 10% and 25% by volume, or between 15% and 25% by volume, or between 15% and 17% by volume, or between 20% and 25% by volume, or between 5% and 20% by volume, or between 14% and 18% by volume, or between 5% and 15% by volume, or between 5% and 10% by volume, or between 15% and 20% by volume.

[0061] Sintered ceramic bodies prepared according to the disclosed methods, and sintered ceramic body components made therefrom, preferably have high density. Density measurements were performed using the Archimedes water immersion method, which is known in the art. The ceramic sintered bodies disclosed herein may have a density of, for example, 98-100%, 99-100%, 99.5-99.99%, or 99.5-100%, which may provide improved resistance to erosion and corrosion effects resulting from plasma and deposition processing.

[0062] The following table provides examples of the densities of large parts made from alumina and zirconia according to the present disclosure.

[0063] [Table 1]

[0064] The relative density (RD) of a given material is defined as the ratio of the density measured using Archimedes' method of a sample to the reported theoretical density of the same material, as shown in the following formula. The volumetric porosity (Vp) is calculated from the density measurements as follows:

[0065]

number

[0066] The high density, and hence high mechanical strength, of the ceramic sintered bodies disclosed herein also provides improved handling, especially in larger dimensions. Successful manufacture of sintered ZTA bodies is achieved by controlling the variation in density across at least one longest dimension (e.g., about 200-625 mm). Average densities of 98.5% or more and 99.5% or more as indicated above can be obtained with a density variation of 5% or less, preferably 4% or less, preferably 3% or less, preferably 2% or less, preferably 1% or less across the largest dimension, whereby the largest dimension may be, for example, about 625 mm or less, 622 mm or less, 610 mm or less, preferably 575 mm or less, preferably 525 mm or less, preferably 100-625 mm, preferably 100-622 mm, preferably 100-575 mm, preferably 200-625 mm, preferably 200-510 mm, preferably 400-625 mm, preferably 500-625 mm. Reducing the density variation improves the handling properties and reduces the stress in the entire sintered ceramic body.

[0067] The ceramic sintered body disclosed herein may have very small pores both on the surface and throughout. Preferably, the ceramic sintered body made according to the process disclosed herein is therefore an integral body with pores distributed uniformly throughout. In other words, the pores or voids or gaps measured on the surface may represent the pores or voids or gaps in the bulk corrosion-resistant layer. Thus, the volumetric porosity present in the bulk ceramic body disclosed herein also represents the gaps measured across the surface.

[0068] Correspondingly, the sintered ceramic bodies disclosed herein have pores or voids, but the level of porosity is very low, which may provide improved performance in plasma etching and deposition applications and facilitate extensive cleaning to the level required for semiconductor processing systems. This results in extended component life, improved process stability, and reduced chamber downtime for cleaning and maintenance. Nearly dense or fully dense solid sintered ceramic bodies with minimal porosity are disclosed herein. This minimal porosity may allow for reduced particle generation by preventing trapping of contaminants at the surface of the sintered ceramic body during etching and deposition processes. In some embodiments, where the sintered ceramic body may serve as a substrate for subsequent deposition of a corrosion resistant layer by aerosol, plasma spray, and other techniques, this low level of porosity may allow for the formation of very thin corrosion resistant films, e.g., about 1-20 μm, which may be uniform and free of voids or gaps.

[0069] Correspondingly, it may be advantageous for the sintered ceramic body to have a small percentage of the surface area made up of pores, in combination with small diameter pores and controlled pore size distribution. The corrosion resistant sintered ceramic bodies disclosed herein may have a porosity of less than 2%, preferably less than 1%, preferably less than 0.5% in the sintered ceramic body, providing improved etch resistance due to the controlled pore area, pore frequency, and fine pore size of the surface. Preferably, the pores have a maximum pore size of 0.1-5 μm, preferably 0.1-4 μm, more preferably 0.1-3 μm, more preferably 0.1-2 μm, and most preferably 0.1-1 μm, as measured by SEM.

[0070] In an embodiment, the porosity across the surface of the sintered ceramic bodies disclosed herein is in an amount of 0.0005-2%, preferably 0.0005-1%, preferably 0.0005-0.5%, preferably 0.0005-0.05%, preferably 0.0005-0.005%, preferably 0.0005-0.003%, preferably 0.0005-0.001%, preferably 0.005-2%, preferably 0.05-2%, preferably 0.5-2%, preferably 0.005-2%, preferably 0.005-1%, preferably 0.05-2%, preferably 0.05-1%, preferably 0.5-2%.

[0071] In addition to high density, high hardness values ​​further provide enhanced resistance to erosion during use as plasma chamber components. Thus, Vickers hardness measurements were performed according to ASTM standard C1327 "Standard Test Method for Vickers Indentation Hardness of Advanced Ceramics". Hardness values ​​of 17-23 GPa, preferably 18-22 GPa, preferably about 20 GPa, can be obtained for the sintered ceramic bodies disclosed herein. These high hardness values ​​can contribute to improved resistance to ion bombardment during semiconductor etching processes and reduced erosion during use, providing extended life when the sintered ceramic bodies are machined into sintered ceramic body components having fine-scale features.

[0072] The sintered ceramic bodies disclosed herein have a melting point of 6.899-9.630×10 over a temperature range from 25-200° C. to 25-1400° C. -6 / °C, in some embodiments 7.113 to 7.326 × 10 -6 / °C, and in other embodiments, 6.685 to 6.899 × 10 -6 / °C, and in other embodiments, 6.685 to 7.113 × 10 -6 / °C, and in other embodiments, 6.685 to 7.54 × 10 -6 / °C, and in still another embodiment, 7.540 to 9.515 × 10 -6 / °C, and in still another embodiment, 7.326 to 9.515 × 10 -6 / °C, and in still another embodiment, 7.113 to 9.515 × 10 -6 / °C, and in still another embodiment, 6.899 to 9.515 × 10 -6 / °C, and in still another embodiment, 6.685 to 9.515 × 10 -6 2, the thermal expansion coefficients are plotted comparing compositions having various amounts of zirconia from 8 to 20 volume percent over the temperature range of 25-200°C to 25-1400°C. The composition of the sintered ceramic body can be tailored to produce specific CTE characteristics based on the volume of zirconia in alumina. The sintered ceramic body has a CTE of approximately 6.899 x 10 for 10 volume percent zirconia from 25-200°C to 25-1400°C, as shown in the table below which lists the data illustrated by FIG. 2. -6 / ℃ to about 9.630 × 10 for about 25 volume percent zirconia -6 The composition of zirconia can be varied up to 100 / °C.

[0073] [Table 2]

[0074] FIG. 6 shows the frequency of total discrete domain area by second phase size and total discrete domain area by second phase size for a second crystalline phase containing discrete domains of zirconia according to embodiments disclosed herein. The maximum frequency of discrete domain area occurs at a count of 244 domains, and therefore this is taken as the average area of ​​discrete domains comprising a second phase as disclosed herein. Thus, in embodiments, disclosed herein is a sintered ceramic body comprising a second crystalline phase having discrete domains, wherein any one domain is greater than 10-30 μm. 2 , preferably 10 to 25 μm 2 , preferably 10 to 20 μm 2 , preferably 15 to 25 μm 2 , preferably about 23 μm 2The average area of ​​the discontinuous regions containing the second crystalline phase allows for the formation of a sintered ceramic body having controlled CTE properties, high fracture toughness, and high strength. The maximum area of ​​the discontinuous regions is, for example, 100 um. 2 If greater, the CTE difference between the first and second crystalline phases can cause cracks in the microstructure adjacent to the large discontinuous regions of the second crystalline phase. The finely dispersed discontinuous regions, as represented by the average and maximum areas of the second crystalline phase, provide the sintered ceramic body with improved fracture toughness and strength. Thus, in an embodiment, the maximum area of ​​the discontinuous regions comprising the zirconia second phase is about 60 um. 2 Less than or equal to 55um, preferably about 2 Less than 50um, preferably about 50um 2 It is preferable that:

[0075] Mechanical strength properties are known to improve with decreasing grain size. To evaluate grain size, linear intercept grain size measurements were performed according to the Heyn Linear Intercept Procedure described in ASTM standard E112-2010 "Standard Test Method for Determining Average Grain Size". To meet the high bending strength and stiffness requirements for use in reactor chambers as large components, e.g., 200-600 mm, the sintered ceramic bodies disclosed herein have fine grain sizes. In an embodiment, the first crystalline phase has a grain size of 1-5 μm, preferably 2-5 μm, preferably 3-5 μm, preferably 1-4 μm, preferably 2-3 μm, and the second crystalline phase has a grain size of 0.5-4 μm, preferably 1-4 μm, preferably 2-4 μm, preferably 0.5-3 μm, preferably 0.5-2 μm, as measured according to ASTM E112-2010. These grain sizes may result in sintered ceramic bodies having a four-point bending strength of 300 MPa or less, preferably 350 MPa or less, preferably at least 400 MPa. Grain sizes that are too large in diameter, on the order of 20 um or more, may result in sintered ceramic bodies having low bending strength values, which may make the bodies unsuitable for use as etching chamber components, particularly of large dimensions, and therefore it is preferred that the sintered ceramic bodies have an average grain size preferably less than 3 um.

[0076] Providing a material with low dielectric loss also becomes important as frequencies increase. The ceramic sintered body disclosed herein has a dielectric loss of about 5×10 over the frequency range of 1 MHz to 20 GHz. -2 ~5×10 -5The dielectric loss can be adjusted within the following specific application ranges. Material properties such as the purity of the starting powder, and in particular the silica content in the sintered ceramic body, can affect the dielectric loss. In an embodiment, a sintered ceramic body that meets the above-mentioned dielectric loss requirements can be provided when the silica content in the starting material is low. In a preferred embodiment, Si is not present in the sintered ceramic body at detectable levels or is present in an amount of 100 ppm or less, for example, 14 ppm to 100 ppm, preferably 14 to 75 ppm, preferably 14 to 50 ppm, preferably 14 to 25 ppm, preferably 14 to 20 ppm. In one embodiment, Si is present in the sintered ceramic body, if at all, at a concentration of 50 ppm or less. In another embodiment, Si is present in the sintered ceramic body, if at all, at a concentration of 14 ppm or less. In another embodiment, Si is present in the sintered ceramic body, if at all, at a concentration of 10 ppm or less. In yet another embodiment, Si is present in the sintered ceramic body, if at all, at a concentration of 7 ppm or less.

[0077] Additionally, dielectric losses can be affected by particle size and particle size distribution. Finer particle sizes can also provide reduced dielectric losses and thereby reduced heating during use at higher frequencies. These material properties can be tailored through material synthesis to meet specific loss values ​​depending on the component application within the process chamber.

[0078] The sintered ceramic bodies disclosed herein may be among the most etch-resistant materials known, and the use of high purity starting materials to produce sintered ceramic bodies of very high purity and density as starting materials provides inherent etch resistance to ceramic sintered components. However, high purity oxides are difficult to sinter to the high densities required for semiconductor etching chamber applications. Since sintering aids are often required to achieve high (>98%, >99%, or >99.5%) densities, the high sintering temperatures and high plasma etch resistance material properties present a challenge in sintering to high densities while maintaining the required high purity. This high purity prevents roughening of the surface of the sintered ceramic body by halogen-based gas species, which may otherwise chemically attack, roughen, and etch components made from less pure powders. For the aforementioned reasons, full purity of >99.99%, preferably >99.999%, preferably >99.9999% may be preferred in alumina and zirconia starting materials. Correspondingly, in embodiments, the alumina and zirconia powders from which the sintered ceramic bodies are made are free of sintering aids, except for magnesia and silica, which may be present in the disclosed ranges.

[0079] The total purity of the sintered ceramic bodies disclosed herein may have a purity of 99.985% or more, 99.99% or more, preferably 99.995% or more, more preferably 99.999% or more. In other words, the sintered ceramic bodies disclosed herein may have a total impurity content of less than 100 ppm, preferably less than 75 ppm, preferably less than 50 ppm, preferably less than 25 ppm, preferably less than 15 ppm, preferably less than 10 ppm, preferably less than 8 ppm, preferably less than 5 ppm, preferably between 5 and 30 ppm, preferably between 5 and 20 ppm, based on the total mass of the sintered ceramic body, as measured using ICPMS techniques. The total impurity content disclosed herein does not include Si in the form of silica.

[0080] In particular, the sintered ceramic bodies disclosed herein have impurities of the trace metals Na, Fe, and Mg of 50 ppm or less as measured by ICPMS. In another embodiment, the sintered ceramic bodies disclosed herein have impurities of the trace metals Na, Fe, and Mg of 5 ppm or less as measured by ICPMS. In yet another embodiment, the sintered ceramic bodies disclosed herein have a purity of the trace elements Li, Na, Mg, K, Ca, B, P, Fe, Cu, Cr, Zn, In, Sn, and Sb (combined) of 50 ppm or less as measured by ICPMS.

[0081] The detection limit using the ICP-MS method disclosed herein to identify the presence of lighter elements is higher than the reporting limit of heavier elements. In other words, heavier elements, such as Sc and above, are detected with a higher precision, such as as low as 0.06 ppm, than lighter elements, such as Li to Al, which are detected with a lower precision, such as as low as 0.7 ppm. Thus, the impurity content of these powders containing lighter elements, such as Li to Al, can be measured to be about 0.7 ppm or higher, and the impurity content of heavier elements, such as Sc (scandium) to U (uranium), can be measured to be about 0.06 ppm or higher. Using the ICPMS method disclosed herein, K (potassium) and Ca (calcium) can be identified in amounts of 1.4 ppm or higher. Iron can be detected with a precision as low as 0.14 ppm. Trace amounts of yttria and hafnia may be present in the sintered ceramic body, as these oxides are often used as stabilizers for zirconia and are therefore not impurities. Apart from the purity of the sintered ceramic body, the purity of the ceramic sintered components can be maintained.

[0082] Thus, the surface of the sintered ceramic body, both before and after the etching process, can be correlated to particulate generation in the processing chamber. Therefore, it is generally beneficial to have reduced surface roughness. The parameters Sa (arithmetic mean height), Sz (maximum height), and Sdr (interface development area) were measured for the sintered ceramic body. In general, the surface roughness after the plasma etching process can affect chamber particulate generation in that the low surface roughness provided by the corrosion-resistant material reduces the release of contaminant particles into the chamber, and correspondingly, the higher surface roughness after etching can contribute to particulate generation and release onto the wafer. In addition, a smoother surface, as indicated by lower surface roughness values ​​of Sa, Sz, and Sdr, allows the chamber components disclosed herein to be more easily cleaned to semiconductor grade levels.

[0083] Surface roughness measurements can be performed using a Keyence 3D laser scanning confocal digital microscope model VK-X250X under Class 1 cleanroom environmental conditions. The microscope sits on a TMC tableTop CSP benchtop passive vibration isolation table with a natural frequency of 2.8Hz. This non-contact system uses a laser beam light and an optical sensor to analyze the surface via the intensity of the reflected light. The microscope acquires 1,024 data points in the x-direction and 786 data points in the y-direction for a total of 786,432 data points. Once a given scan is completed, the objective lens moves in the z-direction by a set pitch and the intensity is compared between scans to determine focus. ISO25178 Surface Texture (Areal Roughness Measurement) is a set of international standards related to the analysis of surface roughness, to which this microscope complies.

[0084] A detailed image of the sample is taken, typically by laser scanning the surface of the sample at 10x magnification using a confocal microscope. Line roughness is obtained in the profile of the seven sectioned blocks. Lambda-chi (λ), which represents the measurement sampling length, can be adjusted so that the line readings are restricted to measurements from five of the seven central blocks according to ISO specification 4288: Specification for geometric properties of products (GPS)--Surface texture: Profile methods--Rules and procedures for the evaluation of surface texture.

[0085] Areas can be selected within the etched and unetched regions of the sample for measurement and used to calculate Sa, Sz and Sdr.

[0086] Sa represents the average roughness value calculated over a user-defined area of ​​the surface of the sintered ceramic body. Sz represents the maximum peak-valley distance over a user-defined area of ​​the surface of the sintered ceramic body. Sdr is a calculated numerical value defined as the "interface development area ratio" and is a proportional representation of the increase in actual surface area relative to a perfectly flat surface. A flat surface is assigned an Sdr of 0, and the value increases with the slope of the surface. A larger numerical value corresponds to a larger increase in surface area. This allows for a numerical comparison of the degree of surface area increase between samples. It represents the additional surface area resulting from texture or surface features compared to a flat area.

[0087] The surface roughness characteristics Sa, Sz and Sdr are parameters known in the underlying technical field and are described, for example, in section 4.3.2 of the ISO standard 25178-2-2012.

[0088] The present disclosure relates to a sintered ceramic body having a corrosion resistant surface prior to an etching or deposition process that provides an arithmetic mean height Sa of less than 30 nm, more preferably less than 20 nm, more preferably less than 15 nm, more preferably less than 12 nm, more preferably less than 10 nm, preferably between 3 and 25 nm, preferably between 3 and 20 nm, preferably between 3 and 10 nm, preferably between 3 and 8 nm, according to section 4.1.7 of ISO standard 25178-2-2012, wherein the surface roughness does not exceed a certain value and the distribution of porosity is controlled.

[0089] The following table lists the Sa, Sz, and Sdr measurements for the sintered ceramic bodies disclosed herein.

[0090] [Table 3]

[0091] The present disclosure relates to a sintered ceramic body having a corrosion resistant surface prior to an etching or deposition process that provides a maximum height Sz of less than 5.0 μm, more preferably less than 4.0 μm, most preferably less than 3.5 μm, more preferably less than 2.5 μm, more preferably less than 2 μm, more preferably less than 1.5 μm, more preferably less than 1 μm according to section 4.1.7 of ISO standard 25178-2-2012, with a surface roughness not exceeding a specific value and a controlled porosity distribution.

[0092] This disclosure is based on ISO standard 25178-2-2012, section 4.1.7, for a 100 × 10 -5 less than 80×10 -5 Less than 600×10 -5 less than 50×10 -5 For a sintered ceramic body having a corrosion resistant surface prior to an etching or deposition process that provides a developed interfacial area Sdr less than 0.05 mm, the surface roughness does not exceed a specified value, and the porosity distribution is controlled.

[0093] In some embodiments where the sintered ceramic body may serve as a substrate for subsequent deposition of a corrosion resistant layer by aerosol, plasma spray, and other techniques, these low values ​​of Sa, Sz, and Sdr disclosed herein may enable the formation of very thin corrosion resistant films, e.g., about 1-20 um, which may be uniform and may be free of voids or gaps.

[0094] Preparation method Sintered ceramic bodies can be prepared using pressure-assisted sintering in combination with DC sintering and related techniques, which use direct current to heat an electrically conductive die arrangement or tool set, thereby sintering the material. This heating regime allows for very high heating and cooling rates to be applied, enhancing densification mechanisms over diffusion mechanisms that drive grain growth, facilitating the preparation of very fine grain sintered ceramic bodies, and transferring the inherent properties of the original powders to their nearly or fully dense products.

[0095] Disclosed is a method of making a sintered ceramic body, the method including the steps of: a) combining aluminum oxide powder and zirconium oxide powder to form a powder mixture, wherein the aluminum oxide powder and zirconium oxide powder each have a total impurity content of less than 150 ppm; b) firing the powder mixture by heating to raise the temperature of the powder mixture to a firing temperature and maintaining the firing temperature to form a fired powder mixture; c) placing the fired powder mixture within a volume defined by a sintering apparatus toolset to create a vacuum condition within the volume; d) applying pressure to the fired powder mixture while heating to the sintering temperature to form a sintered ceramic body; and e) reducing the temperature of the sintered ceramic body. The following additional steps are optional: f) annealing the sintered ceramic body by optionally applying heat to raise the temperature of the sintered ceramic body until an annealing temperature is reached; g) reducing the temperature of the annealed sintered ceramic body to ambient temperature by removing the heat source applied to the sintered ceramic body; and h) machining the sintered ceramic body to create sintered ceramic body components such as dielectric or RF windows, focus rings, nozzles or gas injectors, showerheads, gas distribution plates, etch chamber liners, plasma source adapters, gas inlet adapters, diffusers, electronic wafer chucks, chucks, pucks, mixing manifolds, ion suppressor elements, faceplates, isolators, spacers, and / or guard rings in etch chambers. As a result, a sintered ceramic body having at least one surface, the sintered ceramic body comprising a first crystalline phase comprising Al2O3 and a second crystalline phase comprising 8 volume % to 20 volume % ZrO2, the first crystalline phase being a continuous matrix and the second crystalline phase being dispersed in the continuous matrix, the sintered ceramic body having pores with a maximum pore size of 0.1 to 5 μm as measured by SEM, and the sintered ceramic body having a pore size of 6.899 to 9.630 × 10 over a temperature range of 25-200 °C to 25-1400 °C as measured in accordance with ASTM E228-17. -6 / °C, the sintered ceramic body has a relative density of 99%-100%, has a density variation of less than 0.2-5% across its greatest dimension, the greatest dimension is 200-625 mm, and Si is either absent in the sintered ceramic body or is present in the sintered ceramic body in an amount of 100 ppm or less.

[0096] The above-mentioned properties of the corrosion-resistant component formed from the sintered ceramic body are achieved, inter alia, by adapting the purity of the aluminum oxide and zirconium oxide powders, the pressure on the aluminum oxide and zirconium oxide powders, the temperature of the aluminum oxide and zirconium oxide powders, the duration of sintering the powders, the temperature of the sintered ceramic body / sintered ceramic body component during the optional annealing step, and the duration of the annealing step.

[0097] The methods disclosed herein provide for the preparation of sintered ceramic body components comprised of zirconia-reinforced aluminum oxide. The aforementioned compositions may also be made in some embodiments with an optional rare earth oxide dopant selected from the group consisting of Sc, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Tm, Yb, and Lu and their oxides in an amount of 1 wt.% or less, which may be added to the powder mixture in step a). In some embodiments, the aluminum oxide powder and the zirconium oxide powder are mixed without a dopant.

[0098] The properties of the sintered ceramic body and sintered ceramic body components according to one embodiment are achieved by adapting the steps a) powder mixing / bonding and b) heat treatment of the powder mixture before sintering, the purity, particle size and surface area of ​​the starting aluminum oxide and zirconium oxide powders used in step a), the surface area and uniformity of the starting materials used in step a), the pressure on the powder mixture in step d), the sintering temperature of the powder mixture in step d), the sintering time of the powder mixture in step d), the temperature of the sintered ceramic body or component during the optional annealing step in step f), and the time of the optional annealing step f). The obtained sintered ceramic body can be suitably used as a sintered ceramic body or corrosion-resistant part in plasma processing equipment, especially in semiconductor manufacturing equipment. Such parts or parts may include windows, nozzles, gas injectors, showerheads, (etching) chamber liners, mixing manifolds, wafer supports, electronic wafer chucks, and various rings such as focus rings and guard rings, among other components.

[0099] The ceramic sintered bodies of the present disclosure not only exhibit high strength when used in semiconductor processing tools, but also low loss of RF transmission, a feature that makes them particularly suitable for use as dielectrics or RF windows.

[0100] Step a) of the method disclosed herein comprises combining powders comprising aluminium oxide and zirconium oxide to produce a powder mixture. The aluminium oxide and zirconium oxide starting materials for forming the sinter and / or component are preferably commercially available powders of high purity.

[0101] The particle size of the aluminum oxide powder used as the starting material according to one embodiment is usually 0.05 to 5 μm, preferably 0.1 to 3 μm, and more preferably 0.2 to 2 μm. The aluminum oxide powder usually has a particle size of 1 to 18 μm. 2 / g, more preferably 4 to 16m 2 / g, most preferably 6 to 12 m 2The purity of the aluminum oxide starting material is typically greater than 99.0%, preferably greater than 99.96%, more preferably greater than 99.995%.

[0102] The zirconium oxide powder may have a particle size distribution with a d10 of 0.08-0.20 um, a d50 of 0.3-0.7 um, and a d90 of 0.9-5 μm. The zirconium oxide powder used as starting material for the mixture according to one embodiment of the present invention may have an average particle size of 1-3 um. The zirconia powder typically has an average particle size of 1-16 μm. 2 / g, preferably 2 to 10m 2 / g, more preferably 5 to 8m 2 The purity of the zirconia powder starting material is typically greater than 99.0%, preferably greater than 99.5%, preferably greater than 99.97%, preferably greater than 99.99%.

[0103] The alumina and zirconia powders are mixed in such a ratio that the zirconia is present in the mixture at 5 to 25 volume %, preferably 10 to 25 volume %, preferably 15 to 25 volume %, preferably 20 to 25 volume %, preferably 5 to 20 volume %, preferably 5 to 15 volume %, preferably 5 to 10 volume %, preferably 15 to 20 volume % of the sintered ceramic body, respectively.

[0104] Mixing the alumina powder and the zirconia powder to create a powder mixture can be done using conventional powder preparation techniques of ball milling, wet mixing, and dry mixing. Ball milling can be accomplished using alumina media as an example and can be done according to methods known to those skilled in the art. In other examples, harder media such as zirconium oxide may be used. The use of ball milling is a high energy process that can break down particulates and agglomerates and provide a homogenous powder mixture before firing. Ball milling can be done in either wet or dry conditions. Wet mixing can be done using various solvents, such as ethanol or water, with minimal or no media during mixing and can be done according to methods known to those skilled in the art. Wet mixing improves the dispersion of the powders through increased mobility and provides a fine-scale homogenous mix before heat treatment or firing. Dry mixing can be done with or without media according to the purity requirements in the final sintered ceramic body and can be done according to methods known to those skilled in the art. Additional powder preparation procedures such as attrition milling, high shear mixing, planetary milling, and other known procedures may also be applied. The powder slurry is dried according to known methods. The powder preparation techniques described above may be used alone or in any combination thereof, or for two or more powder mixtures that are subsequently combined into the final sintered ceramic body.

[0105] Step b) of the method disclosed herein is to sinter the powder mixture by heating to raise the temperature of the powder mixture to a sintering temperature and maintaining the sintering temperature. This step may be performed to remove moisture and ensure that the surface condition of the powder mixture is uniform before sintering. The sintering followed by the heat treatment step may be performed in an oxygen-containing environment at a temperature of about 600°C to about 1400°C for 4 to 12 hours. The surface area of ​​the powder mixture may be 1 to 18 m2. 2 / g, 3-15m 2 / g, or 3 to 10m 2 After calcination, the powder may be sieved and / or tumbled according to known methods.

[0106] After calcination, the calcined powder mixture is typically 1 to 12 m 2 / g, preferably 2 to 10m 2 / g, preferably 3 to 9m 2 / g, preferably 4 to 8 m 2 / g.

[0107] Step c) of the method disclosed herein is to place the sintered powder mixture in a volume defined by a tool set of a spark plasma sintering machine to create a vacuum condition environment in the volume. The sintering machine used in the process according to one embodiment includes at least one graphite die, which is usually a cylindrical graphite die. In the graphite die, the powder mixture is placed between two graphite punches or, in some cases, between spacer elements. At least one powder mixture can be loaded into the die of the sintering machine. A vacuum condition known to those skilled in the art is established in the volume created by the punches and the die.

[0108] In a preferred embodiment, a spark plasma sintering (SPS) tool includes a die with a sidewall having an inner wall having a diameter defining an interior volume capable of receiving at least one ceramic powder, and an outer wall, and an upper punch and a lower punch operatively coupled to the die, each of the upper punch and the lower punch having an outer wall defining a diameter smaller than the diameter of the inner wall of the die, thereby defining a gap between each of the upper punch and the lower punch and the inner wall of the die when at least one of the upper punch and the lower punch moves within the interior volume of the die, where the gap has a width of 10 μm to 100 μm. Preferably, the die and punch are made of graphite. Such an SPS tool is disclosed in U.S. Provisional Patent Application No. 63 / 087,204, filed October 3, 2020, which is incorporated herein by reference.

[0109] The disclosed method utilizes commercially available powders or those prepared from chemical synthesis techniques and does not require sintering aids, cold pressing, molding or machining of the white body prior to sintering.

[0110] Step d) of the method involves applying pressure to the sintered powder mixture to sinter it while heating it to a sintering temperature to form a sintered ceramic body, and step e involves reducing the temperature of the sintered ceramic body, for example by removing the heat source to the sintering apparatus and cooling the sintered body. After the powder mixture is placed in the volume defined by the die and punch, pressure is applied to the powder mixture placed between the graphite punch. The pressure is thereby increased to a pressure of 5 MPa to 100 MPa, preferably 10 MPa to 50 MPa, preferably 15 MPa to 45 MPa, preferably 20 to 40 MPa. The pressure is applied axially on the material placed in the die.

[0111] In a preferred embodiment, the powder mixture is heated directly by the punch and die of the sintering apparatus. The die and punch may be constructed of a conductive material such as graphite to facilitate resistive / joule heating. Sintering apparatus and procedures are disclosed in U.S. Patent Application Publication No. 2010 / 0156008(A1), which is incorporated herein by reference.

[0112] The temperatures of the sintering apparatus according to the present disclosure are usually measured in the graphite die of the apparatus, therefore it is preferred that the temperatures are measured as close as possible to the powders being processed so that the temperatures indicated are actually realized in the powder mixture.

[0113] The application of heat to the powder mixture provided in the die facilitates a sintering temperature of about 1000-1700°C, preferably about 1050-1600°C, more preferably about 1300-1500°C. Final sintering may typically be accomplished in a time period of 0.5-1440 minutes, preferably 0.5-720 minutes, preferably 0.5-360 minutes, preferably 0.5-240 minutes, preferably 0.5-120 minutes, preferably 0.5-60 minutes, preferably 0.5-30 minutes, preferably 0.5-20 minutes, preferably 0.5-10 minutes, preferably 0.5-5 minutes. In step e) of the process, the sintered ceramic body is passively cooled by removal of the heat source. Natural convection may occur until a temperature is reached that may facilitate the optional annealing process.

[0114] During sintering, a reduction in volume typically occurs, so that the sintered ceramic body may have a volume that is approximately one-third the volume of the starting powder mixture when placed into the sintering apparatus tool set.

[0115] In one embodiment, the order of application of pressure and temperature may be varied according to the present disclosure, meaning that it is possible to apply the indicated pressure first, followed by application of heat to reach the desired temperature. Additionally, in other embodiments, it is also possible to first apply the indicated heating to reach the desired temperature, followed by application of the indicated pressure. In a third embodiment according to the present disclosure, temperature and pressure may be applied simultaneously to the powder mixture to be sintered, ramping up to the indicated values.

[0116] Induction or radiant heating methods can also be used to heat the sintering apparatus to indirectly heat the powder mixture in the toolset.

[0117] In contrast to other sintering techniques, preparation of the sample prior to sintering, i.e. by cold pressing or molding on a white background, is not mandatory and the premixed powder is directly loaded into a mold, which may provide higher purity in the final sintered ceramic body.

[0118] In further contrast to other sintering techniques, sintering aids are not required. Moreover, high purity starting powders are desirable for optimal etching performance and low RF transmission loss. The absence of sintering aids and the use of high purity starting materials with purities of greater than 99.99% to 99.9999% allow for the production of high purity sintered ceramic bodies that offer improved etch resistance for use as ceramic sintered components in semiconductor etch chambers.

[0119] Therefore, sintering under an isothermal residence time is typically carried out for a period of 0 minutes to 1440 minutes, preferably 0 minutes to 720 minutes, preferably 0 minutes to 360 minutes, preferably 0 minutes to 240 minutes, preferably 0 minutes to 120 minutes, preferably 0 minutes to 60 minutes, preferably 0 minutes to 30 minutes, preferably 0 minutes to 20 minutes, preferably 0 minutes to 10 minutes, preferably 0 minutes to 5 minutes.

[0120] In one embodiment of the present invention, process step d) may further comprise a pre-sintering step with a specific heating gradient between 0.1° C. / min and 100° C. / min, preferably between 1° C. / min and 50° C. / min, more preferably between 2° C. / min and 25° C. / min, until a specific pre-sintering time is reached.

[0121] In a further embodiment of the invention, process step d) may further comprise a pre-sintering step with a specific pressure gradient of 0.50 MPa / min to 30 MPa / min, preferably 0.75 MPa / min to 20 MPa / min, more preferably 1 MPa / min to 10 MPa / min until a specific pre-sintering time is reached.

[0122] In another embodiment, process step d) may further comprise a pre-sintering step using the specific heating gradient mentioned above and the specific pressure gradient mentioned above.

[0123] At the end of process step d), in one embodiment, the method may further comprise step e), cooling the sintered ceramic body by natural cooling of the process chamber under vacuum conditions (non-forced cooling) as known to the skilled person. In a further embodiment according to process step e), the sintered ceramic body may be cooled under convection of an inert gas, for example argon or nitrogen at 1 bar. Other gas pressures above or below 1 bar may also be used. In a further embodiment, the sintered ceramic body is cooled under forced convection conditions in an oxygen environment. To start the cooling step, at the end of sintering step d), the power applied to the sintering device is removed and the pressure applied to the sintered ceramic body is removed, after which the cooling is carried out according to step e).

[0124] Step f) of the method disclosed herein optionally comprises annealing the sintered ceramic body by applying heat to increase the temperature of the sintered ceramic body until an annealing temperature is reached, and step g) comprises decreasing the temperature of the annealed sintered ceramic body. In the optional step f), the sintered ceramic body or component obtained in step d) or h), respectively, can be subjected to an annealing procedure. In other examples, the sintered ceramic body or component may not be annealed. Under other circumstances, the annealing may be performed in a furnace outside the sintering apparatus or in the sintering apparatus itself without removal from the apparatus.

[0125] For the purposes of annealing according to the present disclosure, the sintered ceramic body may be removed from the sintering apparatus after cooling according to process step e) and the process step of annealing may be carried out in a separate apparatus, such as a furnace.

[0126] In some embodiments, for the purposes of annealing according to the present disclosure, the sintered ceramic body in step d) may be annealed subsequently in the sintering apparatus without the need to remove it from the sintering apparatus between the sintering step d) and the optional annealing step f).

[0127] This annealing can improve the chemical and physical properties of the sintered body, the annealing step can be carried out by conventional methods used for annealing glasses, ceramics, and metals, and the degree of improvement can be selected by the selection of the annealing temperature and the duration for which the annealing is continued.

[0128] Typically, the optional step f) of annealing the sintered ceramic body is carried out at a temperature of from about 900 to about 1800°C, preferably from about 1250 to about 1700°C, more preferably from about 1300 to about 1650°C.

[0129] The optional annealing step f) is intended to modify the oxygen vacancies in the crystal structure back to the stoichiometric ratio. The step of annealing the zirconia toughened alumina usually requires 5 minutes to 24 hours, preferably 20 minutes to 20 hours, more preferably 60 minutes to 16 hours.

[0130] Typically, the optional process step f) of annealing the sintered ceramic body is carried out in an oxidizing atmosphere, whereby the annealing process may increase the albedo, reduce stress, improve mechanical handling and reduce porosity. The optional annealing step may also be carried out in air.

[0131] After the optional process step f) of annealing the sintered ceramic body, the temperature of the sintered, and in some cases annealed, sintered ceramic body is reduced to ambient temperature according to process step g) and the sintered, and optionally annealed, ceramic body is removed from the furnace if the annealing step is performed outside the sintering apparatus, or removed from the tool set if the annealing step f) is performed within the sintering apparatus.

[0132] Step h) of the method disclosed herein is optionally machining the sintered ceramic body to produce ceramic sintered components, which may be performed according to known methods for machining corrosion-resistant components from the sintered ceramic bodies disclosed herein, including zirconia-toughened alumina. The corrosion-resistant ceramic sintered components required for semiconductor etch chambers may include, among other components, RF or dielectric windows, nozzles or injectors, showerheads, (etch) chamber liners, mixing manifolds, wafer supports, electronic wafer chucks, and various rings such as focus rings and guard rings.

[0133] The sintered ceramic bodies / components have sufficient mechanical properties to allow the manufacture of large body sizes for use in plasma etching and deposition chambers. The components disclosed herein may have sizes of 200 mm to 600 mm, preferably 300 to 600 mm, preferably 350 to 600 mm, preferably 400 to 600 mm, more preferably 450 to 600 mm, more preferably 500 to 600 mm, more preferably 550 to 600 mm, each with respect to the maximum dimension of the sintered body.

[0134] The methods disclosed herein provide improved control over maximum pore size, higher density, improved mechanical strength, and therefore improved handleability of the corrosion-resistant ceramic sintered components, particularly for ceramic bodies with dimensions over 200 mm, for example, over maximum feature size, and reduced oxygen vacancies in the lattice of the corrosion-resistant ceramic sintered components.

[0135] The embodiments of the sintered ceramic bodies disclosed herein can be combined in any particular sintered ceramic body. Thus, two or more of the features disclosed herein can be combined to more specifically describe the sintered ceramic body, for example as outlined in the embodiments.

[0136] Also disclosed herein is a sintered ceramic body prepared by a method including: a) combining aluminum oxide powder and zirconium oxide powder to form a powder mixture, wherein the aluminum oxide powder and the zirconium oxide powder each have a total impurity content of less than 150 ppm; b) firing the powder mixture by heating to raise the temperature of the powder mixture to a firing temperature and maintaining the firing temperature to form a fired powder mixture; c) placing the fired powder mixture within a volume defined by a toolset of a sintering apparatus to create a vacuum condition within the volume; d) applying pressure to the fired powder mixture while heating to the sintering temperature to form a sintered ceramic body; and e) reducing the temperature of the sintered ceramic body. EXAMPLES

[0137] The general nature of the present disclosure is more clearly illustrated in the following examples, which are intended to illustrate, but not limit, the present disclosure.

[0138] The SPS tool used in each of the following examples includes a die with a sidewall having an inner wall having a diameter defining an interior volume capable of receiving at least one ceramic powder, and an outer wall, and an upper punch and a lower punch operatively connected to the die, each of the upper punch and lower punch having an outer wall defining a diameter smaller than the diameter of the inner wall of the die, thereby defining a gap between each of the upper punch and lower punch and the inner wall of the die as at least one of the upper punch and lower punch moves within the interior volume of the die, where the gap has a width of 10 μm to 100 μm.

[0139] The particle sizes of the starting powders, powder mixtures and calcined powder mixtures were measured using a Horiba Model LA-960 laser scattering particle size distribution analyzer capable of measuring particle sizes from 10 nm to 5 mm. The specific surface areas of the starting powders, powder mixtures and calcined powder mixtures ranged from 0.01 to 2000 m for most samples. 2 The specific surface area (SSA) measurements were performed according to ASTM C1274.

[0140] Example 1: Wet ball milling 6~8m 2 zirconia powder having a specific surface area of ​​6 to 8 m / g, a d10 particle size of 0.5 to 0.2 um, a d50 particle size of 0.2 to 0.5 um, and a d90 particle size of 1.2 to 3 um; 2Alumina powder having a specific surface area of ​​0.05-0.15 um / g, a d10 particle size of 0.05-0.15 um, a d50 particle size of 0.2-0.5 um, and a d90 particle size of 0.4-1 um are weighed and combined to create a powder mixture in a molar ratio that forms a zirconia-strengthened aluminum phase upon sintering, where the zirconia is present at 8-20% by volume. The zirconia powder contains about 2% by weight hafnium in solid solution and is stabilized with 3% by mole yttrium oxide. HfO2 and yttria are not considered impurities in the zirconia disclosed herein. The reporting limits for detecting the presence of lighter elements using ICPMS disclosed herein are higher than the reporting limits for heavier elements. In other words, according to the tables herein, heavier elements such as Sc and above are detected with greater accuracy than lighter elements such as Li through Ca. Although these lighter elements such as Si, Na, Ca, and Mg may be present in amounts below the reporting limit or may not be detected, the amounts of these elements may be reported with a level of accuracy of about 14 ppm or higher. Since Si, Ca, Na, and Mg were not detected in the zirconia and alumina powders using ICPMS known to those skilled in the art, the zirconia and alumina powders may contain about 14 ppm or less of Si, Ca, Na, and / or Mg in the form of silica, calcia (CaO), Na2O, and magnesia. With the exception of HfO2, yttria, and the lighter elements as defined herein, the zirconia powder had a total impurity of about 20 ppm. The powder mixture is transferred to a plastic container for wet ball milling using high purity (>99.99%) alumina media at a loading of 75-80% by powder weight and ethanol as the solvent. Ball milling is carried out for 20 hours, after which the ethanol is extracted from the powder mixture using a rotary evaporator. The dried powder mixture was sieved into granules of about 100um and calcined at 600°C for 8 hours. After calcination, the powder mixture was dry blended by tumbling and finally sieved to granulate particles of 100-400um. The physical and chemical properties were then measured from the powder in this state. The calcined powder mixture was then sintered under vacuum at a temperature of 1600°C and a pressure of 15MPa for 60 minutes according to the method disclosed herein.

[0141] The purity of the calcined powders is shown in the table below, which contains ICPMS data for three powder lots after calcination in PPM, with no NDs detected. Elements not listed in the table are below the detection limit of the method and apparatus and therefore are not included.

[0142] [Table 4]

[0143] The above calcined powder mixture was then sintered under vacuum at a temperature of 1450° C. and a pressure of 30 MPa for 30 minutes according to the method disclosed herein. The densities of the sintered ceramic body embodiments are reported in the table below. Theoretical densities were calculated according to the volumetric mixing rules known to those skilled in the art. The measured properties of the sintered ceramic body according to Example 1 are summarized below:

[0144] [Table 5]

[0145] Figure 3 is an SEM micrograph (5000x) of the surface of a sintered ceramic body made according to the present disclosure containing 16% by volume ZrO2, showing a dense (approximately 99% dense) body with a very low level of porosity and, to the extent that it exists, very small pore sizes.

[0146] Figure 4 is a plot of pore area versus pore size for eight images taken from the surface of a sample with 16 vol.% ZrO2, with the dark line representing the average based on the eight images analyzed. In Figure 4, the total surface area is 1.03 μm2 at a pore diameter of 0.2 μm. 2 The measurements were made over eight images taken at 5000x magnification, each with an area of ​​53.7 μm × 53.7 μm, for a total measured area of ​​approximately 2884 μm. 2 A maximum pore size of 0.5 um was measured across the images taken and therefore the plot in Figure 4 has an x-axis limit of 0.5 um.

[0147] FIG. 5 is a graph showing the XRD pattern of a sintered ceramic body made according to the present disclosure containing 15% by volume ZrO2. The XRD pattern shows two crystalline phases, alumina and zirconia, with very little yttria (0.0545) since it is used as a stabilizer for zirconia. X-ray diffraction was performed using a PANanlytical Aeris model XRD that allows crystalline phase identification to about + / - 5%. The sintered ceramic body disclosed herein may include a particle composite of crystalline phases of zirconia and alumina in the disclosed volumetric amounts. The particle composite may include particles or domains of zirconia dispersed in a matrix of alumina, the particle composite including two distinct crystalline phases, and preferably the sintered ceramic body does not form a solid solution. The formation of a solid solution may reduce thermal conductivity, therefore the sintered ceramic body preferably includes distinct crystalline phases of zirconia and alumina. For thermal conductivity reasons, there may be no practical lower limit to the minimum amount of zirconia in the sintered ceramic body, but to provide high thermal conductivity on the order of that of alumina, a sintered ceramic body containing about 10% to 25% by volume of a first crystalline phase of zirconia and the remainder about 75% to 90% by volume of a second crystalline phase of alumina may be preferred. Sintered ceramic bodies having more than about 25% to 30% by volume of zirconia may not provide sufficient thermal conductivity for use, for example, as a component in a semiconductor processing chamber where high thermal conductivity is required. Thus, the sintered ceramic body contains zirconia in an amount of 16% by volume. Furthermore, the use of MgO and / or silica as sintering aids may result in a low thermal conductivity glassy phase present between the particles, thus adversely affecting thermal conductivity and corrosion and erosion resistance.

[0148] Thermal conductivity measurements were performed according to ASTM E1461-13 at ambient temperature and at temperatures of 200° C., measuring values ​​of 27 and 14 W / mK, respectively, for a sintered ceramic body disclosed herein containing about 16 volume percent zirconia and the remainder alumina. Sintered ceramic bodies having compositions within the ranges disclosed herein provide sufficient thermal conductivity for use in chamber components where high thermal conductivity is required.

[0149] The following table lists material properties for a sintered ceramic body containing about 16% ZrO2 in an alumina matrix. Sintered objects formed from the sintered ceramic bodies disclosed herein can have the high strength and increased stiffness / Young's modulus properties necessary for the application of these bodies in the manufacture of objects with large dimensions. The sintered ceramic bodies disclosed herein can provide mechanical strength and stiffness / Young's modulus within the range of mechanical strength and stiffness / Young's modulus of alumina while providing the ability to tailor the coefficient of thermal expansion (CTE) over a temperature range of 25-200 to 25-1400°C according to application specific requirements. The use of the sintered ceramic bodies disclosed herein can significantly increase the strength and stiffness of large dimension articles.

[0150] [Table 6]

[0151] The high density, close to and up to 100% of theoretical, and associated low porosity of the sintered ceramic bodies disclosed herein provide very low water absorption, as shown in the table above. The low water absorption properties of the sintered ceramic bodies disclosed herein may allow for the formation of very thin and uniform corrosion resistant films. Thus, in the embodiments disclosed herein, the sintered ceramic bodies contain water in an amount of 0-0.8%, preferably 0-0.5%, preferably 0-0.3%, preferably 0.1-0.3%, preferably 0-0.1%, based on the percent theoretical density disclosed herein.

[0152] A number of embodiments have been described as disclosed herein. However, it is understood that various modifications can be made without departing from the spirit and scope of the embodiments disclosed herein. Accordingly, other embodiments are within the scope of the following claims.

Claims

1. A sintered ceramic body having at least one surface, the sintered ceramic body comprising Al 2 O 3 A first crystal phase including 8% by volume to 20% by volume of ZrO 2 and a second crystalline phase comprising: -6 1. A sintered ceramic body having a thermal expansion coefficient of 0.1 / °C, wherein the body has a relative density of greater than 98% and a density variation of 2% or less across its greatest dimension, the greatest dimension being between 200 and 625 mm, and wherein Si is either absent in the body or present in the body in an amount of 100 ppm or less.

2. 2. The sintered ceramic body of claim 1, wherein Si, if present, is present at 14 ppm or less.

3. 3. The sintered ceramic body of claim 1 or 2 having a total impurity content of the trace elements Li, Na, Mg, K, Ca, B, P, Fe, Cu, Cr, Zn, In, Sn, and Sb (combined) of 50 ppm or less as measured by ICPMS.

4. 4. The sintered ceramic body according to claim 1, wherein the maximum pore size is from 0.1 to 3 μm as measured by SEM.

5. 5. The sintered ceramic body according to claim 1, wherein the sintered ceramic body has an arithmetic mean height (Sa) of the unetched areas of 3 to 20 nm.

6. The sintered ceramic body according to any one of claims 1 to 5, having a maximum height Sz of 0.05 to 1.5 um in the unetched areas according to section 4.1.7 of ISO standard 25178-2-2012.

7. 7. The sintered ceramic body of any one of claims 1 to 6, having a purity of 99.985% and higher.

8. 8. The sintered ceramic body of claim 1, having a thermal conductivity of about 27 W / mK at 20° C., as measured according to ASTM E1461-13.

9. 9. The sintered ceramic body of claim 1, having a thermal conductivity of about 14 W / mK at 200° C., as measured according to ASTM E1461-13.

10. The ZrO 2 and a second crystalline phase comprising: -6 The sintered ceramic body according to any one of claims 1 to 9, wherein the temperature is 100°C or higher.

11. 1. A method of making a sintered ceramic body, the method comprising: a) combining aluminum oxide powder and zirconium oxide powder to form a powder mixture, the aluminum oxide powder and the zirconium oxide powder each having a total impurity content of less than 150 ppm; b) calcining the powder mixture by heating to raise the temperature of the powder mixture to a calcination temperature of 600° C. to 1400° C. and maintaining the calcination temperature for a period of 4 to 12 hours to effect calcination to form a calcined powder mixture; c) placing the fired powder mixture within a volume defined by a toolset of a sintering machine and creating a vacuum condition within the volume, the toolset comprising a graphite die defining the volume and first and second punches operatively coupled to the die, the die having an inner wall and first and second openings, each of the first and second punches having an outer wall defining a diameter smaller than a diameter of the inner wall of the die, thereby creating a gap between each of the first and second punches and the inner wall of the die as at least one of the first and second punches moves within the volume of the die, the gap being between 10 μm and 100 μm in width; d) sintering the fired powder mixture by applying a pressure of 5 MPa to 100 MPa while heating the mixture to a sintering temperature of 1000 to 1700° C. to form the sintered ceramic body; e) reducing the temperature of a sintered ceramic body, the sintered ceramic body having at least one surface, the sintered ceramic body being made of Al 2 O 3 A first crystal phase including 8% by volume to 20% by volume of ZrO 2 and a second crystalline phase comprising: -6 / °C, wherein the sintered ceramic body has a relative density greater than 98% and a density variation of 2% or less across its greatest dimension, the greatest dimension being between 200 and 625 mm, and Si is either absent in the sintered ceramic body or is present in the sintered ceramic body in an amount of 100 ppm or less; A method comprising:

12. Further steps of: f) annealing the sintered ceramic body by applying heat to raise the temperature of the sintered ceramic body until an annealing temperature is reached; g) reducing the temperature of the annealed sintered ceramic body. The method of claim 11 , comprising:

13. Further steps of: h) machining the sintered ceramic body to produce sintered ceramic components in the form of dielectric or RF windows, focus rings, nozzles or gas injectors, showerheads, gas distribution plates, etch chamber liners, plasma source adapters, gas inlet adapters, diffusers, electronic wafer chucks, chucks, pucks, mixing manifolds, ion suppressor elements, faceplates, isolators, spacers, and / or guard rings in etch chambers. The method of claim 11 or 12, comprising:

14. The method according to any one of claims 11 to 13, wherein the sintering temperature is from 1000 to 1300°C.

15. 15. The method according to any one of claims 11 to 14, wherein a pressure of 5 to 59 MPa is applied to the sintered powder mixture while heating to the sintering temperature.

Citation Information

Patent Citations

  • Alumina-zirconia composite sintered form and production thereof

    JP1989083566A

  • Ceramic granule for press molding

    JP2006027914A

  • Alumina sintered body

    JP2020050536A